Artificial Intelligence and Children's Human Rights - Mahzad Saffarinia (حقوق فناوریهای نوین)
Machine learning technologies are expected to increasingly affect people's daily lives. The next generation of children will be most affected by this technology; because they will be born and raised in an era of big data and machine systems that will affect their life decisions from education, access to credit and job opportunities, and many other things. In this article, the effects of artificial intelligence on children's human rights have been investigated and solutions have been tried to protect children's rights in the dynamic world of technology and artificial intelligence. In addition, the impact and interaction with human rights and especially children's right to education and respect for privacy, freedom of expression, and prohibition of discrimination are important issues that the main guardians such as companies, parents, and governments should address.